The role of the professional catholic associations in spreading christian ethics in society - Joblin, Joseph (Medicina e Morale, 1990)
Christians, especially in a democratic and pluralistic society, should be in a position both to make their point of view heard and to participate in decision-making. Catholic professional associations allow Catholics to take part in public debate. The teaching of recent Popes on this point confirms the thought of the socio-political order.